2016
DOI: 10.1097/mbc.0000000000000479
|View full text |Cite
|
Sign up to set email alerts
|

Nonactivated thromboelastometry able to detect fibrinolysis in contrast to activated methods (EXTEM, INTEM) in a bleeding patient

Abstract: Rotational thromboelastometry (ROTEM) is increasingly used in practice to monitor coagulation status of severely bleeding patients and it helps to provide aimed therapy. The main advantage of ROTEM is detection of fibrinolysis. To get fast results, the reagents for activation, either extrinsic or intrinsic pathway of coagulation, are used. Although this method gives information about whole blood coagulation, in some cases, the patient is bleeding despite normal values of ROTEM. We present a case of a bleeding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 6 publications
0
22
0
Order By: Relevance
“…25,26 27 Data suggest that the NATEM method is more sensitive to changes in coagulation than the activated counterparts. 28 The parameters of clot formation defined by ROTEM are CT, clot formation time (CFT), maximum clot firmness (MCF), and the clot lysis index. 26 The TGA is usually triggered by tissue factor (TF) (extrinsic pathway) or FXIa (intrinsic pathway), leading to thrombin generation, which is monitored over time.…”
Section: Current Methods In the Coagulation Laboratorymentioning
confidence: 99%
“…25,26 27 Data suggest that the NATEM method is more sensitive to changes in coagulation than the activated counterparts. 28 The parameters of clot formation defined by ROTEM are CT, clot formation time (CFT), maximum clot firmness (MCF), and the clot lysis index. 26 The TGA is usually triggered by tissue factor (TF) (extrinsic pathway) or FXIa (intrinsic pathway), leading to thrombin generation, which is monitored over time.…”
Section: Current Methods In the Coagulation Laboratorymentioning
confidence: 99%
“…Raza et al raised the suspicion that ROTEM is simply insensitive until fibrinolysis activation reaches a certain threshold (18). The lack of sensitivity of ROTEM for detecting moderate hyperfibrinolysis with clinical impact in critically ill patients was also described by Durila (19). In a study using thrombelastography in trauma patients, Chapman demonstrated that lower thresholds than the accepted normal upper bound of lysis index are associated with worse outcomes and suggested that clinically relevant threshold for defining hyperfibrinolysis might be lower than the actual standard definition (20).…”
Section: Discussion Discussionmentioning
confidence: 95%
“…They require the use of a reagent (recombinant tissue factor and polybrene/ellagic acid respectively) in addition to calcium; as such the results could be influenced and not precisely reflect the hemostatic status of the patient. There are studies, including patients, where EXTEM/INTEM parameters were within normal range although patients were bleeding actively [ 25 ]. On the other hand the NATEM assay is only activated by calcium without a supplemental reagent (star-tem ® reagent).…”
Section: Discussionmentioning
confidence: 99%